It’s not just what you say: the impact of message tone on intra-party endorsements - Vizcarrondo, Tom; Minooie, Milad (Frontiers in Political Science, 2024)
This study expands previous research on political endorsements by focusing on the tone of the endorsement, rather than the endorser or the presence/absence of any endorsement at all. Using a 2×2 experimental design and a sample of 906 registered voters from a midwestern U.S. state, this study measures the effect of positive and negative endorsements on the voter perceptions of the endorsee, endorser, and unendorsed candidate during a partisan primary election campaign. Results support the idea that positive endorsements generally improve voters’ attitudes toward the endorsee and the endorser and negative endorsements generally hurt voters’ perception of the unendorsed candidate. Further interaction analyses show that factors such as a voter’s existing enthusiasm for politics, government, and politicians can moderate the effect of endorsements. The findings are in line with the proposition of the Social Judgment Theory and support the existing literature on the effect of endorsements.